The Origin of Parasitism Gene in Nematodes: Evolutionary Analysis through the Construction of Domain Trees. (January 2013) - Yang, Yizi; Luo, Damin
Inferring evolutionary history of parasitism genes is important to understand how evolutionary mechanisms affect the occurrences of parasitism genes. In this study, we constructed multiple domain trees for parasitism genes and genes under free-living conditions. Further analyses of horizontal gene transfer (HGT)-like phylogenetic incongruences, duplications, and speciations were performed based on these trees. By comparing these analyses, the contributions of pre-adaptations were found to be more important to the evolution of parasitism genes than those of duplications, and pre-adaptations are as crucial as previously reported HGTs to parasitism. Furthermore, speciation may also affect the evolution of parasitism genes. In addition, Pristionchus pacificus was suggested to be a common model organism for studies of parasitic nematodes, including root-knot species. These analyses provided information regarding mechanisms that may have contributed to the evolution of parasitism genes.